Literasi Keuangan dalam Pengelolaan Keuangan Pribadi Mahasiswa pada Program Studi DIII Administrasi Bisnis Politeknik Negeri Sriwijaya - Tika Handayani; Adellia Suhermanto; Sunanto Sunanto (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2026)
The purpose of this Community Service (PkM) activity is to provide students Diploma III Business Administration Study Program at Sriwijaya State Polytechnic with understanding and insight into the importance of financial literacy in managing personal finances. The methods used in this activity included lectures, discussions, and evaluations. The results of the activity showed an increase in participants' knowledge regarding financial literacy in personal financial management. Based on the material presented, participants understood the importance of financial literacy and its application in managing personal finances more effectively. Furthermore, the discussion results indicated that most participants were previously unfamiliar with the concept of financial literacy. However, financial literacy is a fundamental need that is important for every individual to have in order to avoid various financial problems. Financial problems are not only influenced by income levels but can also be caused by inappropriate financial management, such as errors in managing expenses according to needs, delays in fulfilling payment obligations, and a lack of financial planning for future needs.